Inclusive English Learning For Students With Disabilities: Challenges And Solutions In The Digital Age - Lewaherilla, August (Journal of Pedagogi, 2025)
Inclusive English language learning in the digital era has strategic urgency because it functions not only as a means of global communication but also as a gateway to equal education, employment, and social participation for students with disabilities. However, its implementation still faces various obstacles, ranging from pedagogical limitations of teachers, a lack of assistive technology infrastructure, to low digital literacy. This situation is further complicated by social stigma and gaps in technology access that widen inequalities. Although digital technology offers opportunities through features such as speech-to-text, screen readers, and interactive media, their utilization is often suboptimal due to limited resources and teacher preparedness. This study uses a qualitative approach with a literature review method to examine the challenges and solutions for inclusive English language learning. The analysis was conducted thematically by reviewing relevant academic literature from 2015–2025. The results of the study indicate that inclusive English language learning requires systemic transformation that includes strengthening teacher capacity, providing disability-friendly technology, improving infrastructure, and creating a stigma-free school culture. The principles of Universal Design for Learning (UDL) are recommended as a curriculum framework that ensures equal access for all learners from the outset. Thus, true inclusivity can only be realized through sustained pedagogical, technological, and policy integration.